The Effectiveness of Auditory Intellectually Repetition Learning Model Assisted by Kokami Media in Improving the Speaking Skills of Drama Material for Students of Class VIII Bhakti Mulya - Fhatwah, Risma; Herlina, Dewi; Rosalina, Sinta (FKIP - Universitas Riau, 2025)
This study is motivated by the low speaking ability of students so this study aims to determine the effectiveness of using the Auditory Intellectually Repetition learning model in improving students' speaking ability. This research uses a quantitative quasi-experimental approach with a Non-equivalent control group design. The samples in this study were Bhakti Mulya Junior High School students, class VIII A as the experimental class and class VIII D as the control class. The data collection technique in this study used a test technique in the form of a drama performance which was assessed from 6 aspects of assessment consisting of lafaz, vocabulary, structure, fluency, content, and understanding. The results showed that the Auditory Intellectually Repetition learning model was effective in improving students' speaking ability. This is evidenced by the average post-test score in the experimental class reaching 87.90 and in the control class the average post-test result is 70.67. Independent Sample T Test results with a significance level of 5% of 0.000 ˂ 0.005 were also obtained. This shows that Ha is accepted and HO is rejected. The N-Gain results show that the average N-Gain value for the experimental class of 74% is included in the moderately effective category. Based on the results of the data analysis that has been done, it can be concluded that the Auditory Intellectually Repetition learning model is quite effective in improving the speaking skills of 8th grade students of Bhakti Mulya Junior High School.